Genome-Wide Expression Analysis Indicates that FNR of Escherichia coli K-12 Regulates a Large Number of Genes of Unknown Function - Kang, Yisheng (American Society for Microbiology, 2005)
The major regulator controlling the physiological switch between aerobic and anaerobic growth conditions in Escherichia coli is the DNA binding protein FNR. To identify genes controlled by FNR, we used Affymetrix Antisense GeneChips to compare global gene expression profiles from isogenic MG1655 wild-type and Δfnr strains grown in glucose minimal media under aerobic or anaerobic conditions. We found that 297 genes contained within 184 operons were regulated by FNR and/or by O(2) levels. The expression of many genes known to be involved in anaerobic respiration and fermentation was increased under anaerobic growth conditions, while that of genes involved in aerobic respiration and the tricarboxylic acid cycle were repressed as expected. The expression of nine operons associated with acid resistance was also increased under anaerobic growth conditions, which may reflect the production of acidic fermentation products. Ninety-one genes with no presently defined function were also altered in expression, including seven of the most highly anaerobically induced genes, six of which we found to be directly regulated by FNR. Classification of the 297 genes into eight groups by k-means clustering analysis indicated that genes with common gene expression patterns also had a strong functional relationship, providing clues for studying the function of unknown genes in each group. Six of the eight groups showed regulation by FNR; while some expression groups represent genes that are simply activated or repressed by FNR, others, such as those encoding functions for chemotaxis and motility, showed a more complex pattern of regulation. A computer search for FNR DNA binding sites within predicted promoter regions identified 63 new sites for 54 genes. We suggest that E. coli MG1655 has a larger metabolic potential under anaerobic conditions than has been previously recognized.